COVID‐19: Current knowledge in clinical features, immunological responses, and vaccine development. Issue 3 (12th February 2021) - Singh, Ramandeep; Kang, Alisha; Luo, Xiangqian; Jeyanathan, Mangalakumari; Gillgrass, Amy; Afkhami, Sam; Xing, Zhou
Abstract: The COVID‐19 pandemic has unfolded to be the most challenging global health crisis in a century. In 11 months since its first emergence, according to WHO, the causative infectious agent SARS‐CoV‐2 has infected more than 100 million people and claimed more than 2.15 million lives worldwide. Moreover, the world has raced to understand the virus and natural immunity and to develop vaccines. Thus, within a short 11 months a number of highly promising COVID‐19 vaccines were developed at an unprecedented speed and are now being deployed via emergency use authorization for immunization. Although a considerable number of review contributions are being published, all of them attempt to capture only a specific aspect of COVID‐19 or its therapeutic approaches based on ever‐expanding information. Here, we provide a comprehensive overview to conceptually thread together the latest information on global epidemiology and mitigation strategies, clinical features, viral pathogenesis and immune responses, and the current state of vaccine development.